Elementary level of communicative competence as the aim of teaching English at preschool stage - Kostina, Ye.A.; Kokhanover, T.A. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
Article is devoted to studying of the concept «elementary level of communicative competence» on the basis of the international classification of levels of proficiency in English and the standard training program of preschool institutions of the Republic of Kazakhstan. As a result of comparison of these documents was given the definition of a concept and offered the description of elementary level of communicative competence in preschool organizations of Kazakhstan. On the basis of contradiction, found in the standard program and the international requirements to training in English at this step, the content of training in English in preschool institutions providing not only qualitative results of training, but also preparation for assimilation of the school program.
Коммуникативтік құзыреттің қарапайым деңгейі мектепке дейінгі кезеңде ағылшын тіліне оқытудың мақсаты ретінде
Элементарный уровень коммуникативной компетенции как цель обучения английскому языку на дошкольном этапе
Keywords: elementary level of communicative competence; preschool education; levels of proficiency in English